Strategi Implementasi Elektronifikasi Transaksi Pemerintah Daerah (ETPD) pada Penerimaan Retribusi Pelayanan Persampahan / Kebersihan Kota Tangerang - Fahrinda, Yeni; Giyanto, Bambang; Asropi, Asropi (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2024)
This research was conducted to determine the conditions for the implementation of Local Government Transaction Electronification (ETPD), supporting and inhibiting factors for implementation, identifying strategies can be implemented to optimize ETPD in the revenue of waste/cleaning retribution levies in Tangerang City. The research results were obtained using qualitative methods. This research shows that the implementation of ETPD in the revenue of waste/cleaning retribution levies in Tangerang City is still not optimal, there are 4 (four) aspects that are factors in efforts to implement ETPD, bureaucratic structure, disposition, resources and communication. There were 5 (five) strategy formulations for optimization efforts, (1) Continuing outreach activities, (2) Expanding cooperation, (3) Providing technical guidance/training, (4) Developing infrastructure, and (5) Providing public complaint services.